Peran Whatsapp Gateway dalam Implementasi Kerja Sama Kantor Imigrasi Kelas I Non TPI Pemalang dengan Pemerintah Kabupaten Batang: (Studi Kasus Mal Pelayanan Publik Batang) - Nikko Anung Saktiawan; Seno Setyo Pujonggo; Agung Sulistyo Purnomo (Journal of Mandalika Literature, 2024)
This article examines the role of WhatsApp Gateway innovation in the implementation of cooperation between the Pemalang Class I Non TPI Immigration Office and the Batang Regency Government, focusing on the Batang Regency Public Service Mall (MPP). WhatsApp Gateway is used to improve the efficiency of passport services through an online queuing system. This research uses qualitative methods with data analysis from various sources to assess the effectiveness of this innovation. The results showed that the use of WhatsApp Gateway succeeded in improving the efficiency and quality of public services at the MPP of Batang Regency, while strengthening the collaboration between the Immigration Office Class I non TPI Pemalang and the Batang Regency Government. Artikel ini mengkaji peran inovasi WhatsApp Gateway dalam implementasi kerja sama antara Kantor Imigrasi Kelas I Non TPI Pemalang dengan Pemerintah Kabupaten Batang, yang difokuskan pada Mal Pelayanan Publik (MPP) Kabupaten Batang. WhatsApp Gateway digunakan untuk meningkatkan efisiensi layanan paspor melalui sistem antrean online. Penelitian ini menggunakan metode kualitatif dengan analisis data dari berbagai sumber untuk menilai efektivitas inovasi ini. Hasil penelitian menunjukkan bahwa penggunaan WhatsApp Gateway berhasil meningkatkan efisiensi dan kualitas pelayanan publik di MPP Kabupaten Batang, sekaligus memperkuat kolaborasi antara Kantor Imigrasi Kelas I non TPI Pemalang dengan Pemerintah Kabupaten Batang.